Quasi-transfer of helicopter training from fixed- to motion-base simulator - Fabbroni, D.; Geluardi, S.; Gerboni, C.A.; Olivari, M.; Pollini, L.; Bülthoff, H.H. (My University, 2017)
This paper presents the experimental evaluation of a previously developed hover training program, designed for fixed-base helicopter simulators. In particular, it is investigated whether the skills developed on the fixed-base simulator are transferred to a highly realistic simulator (quasi-Transfer-of-Training experiment). The higher realism was achieved by using the motion-base MPI CyberMotion Simulator. Student pilots participants were asked to perform the hover maneuver controlling an identified model of a Robinson R44 civil light helicopter. Results showed that the skills acquired during fixed-base training were successfully transferred to the highly-realistic condition. The additional motion feedback helped participants achieve better levels of performance.